Prevalence and Associated Risk Factors of Depression among Public Secondary School Females Students in Majmaah, Saudi Arabia - Fahad A Almatham, Salma H.Almutairi, Huda Hakim Abdelrahman, Renad B Alanazi, Ohood L Almimony, Sarah S Almotairi, Atheer M Al-Obaid, Abdulmalik B Albaker, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Depression is a state of low mood for more than two weeks associated with feelings of sadness or a loss of interest in activities once enjoyed. It can lead to a variety of emotional and physical problems and can decrease a person’s ability to function at work and home. Depression is more common among females than males and many risk factors contribute to depression. Objectives: To study the prevalence and associated risk factors of depression among public secondary school female students in Majmaah city in the duration of 2019-2020. Methodology: Descriptive cross-sectional institutional-based study among public secondary school female students in Majmaah city was performed from 2019-2020. The sample was 400 students, randomly selected from 6 secondary schools, and the consent form was taken from each participant. The permission was taken from the ethical committee in the university. Result: There were 400 students involved in this study, based on findings shows that 32.25% of the students were having depression while 67.75 have no depression .It was found that most of the students had the risk factors that could be associated with depression such as losing an important person in their life, 38.8% (n=155); life stress, 26.5% (n=106); previous episodes of depression or anxiety, 26.8% (n=107); problems at school or with friends, 20.5% (n=82); family problems, 14% (n=56); and exposure to bullying, 11.3% (n=45). Conclusion: Based on findings, 32.25% of the students were having depression while 67.75 have no depression. The majority of them had mild depression 36.50%, 17.75 % had moderate depression, 11.75% had moderately severe depression, and 2.75% had severe depression.